2018
DOI: 10.1177/1747954118787949
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships among the coaching climate, life skills development and well-being in sport

Abstract: Using Benson and Saito’s framework for positive youth development, we investigated the relationships between the coaching climate, young people’s perceived life skills development within sport, and their psychological well-being. British youth sport participants ( N = 326, Mage = 13.81, range = 11–18 years) completed a survey assessing the coaching climate, participants’ perceived life skills development (teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 50 publications
10
54
1
5
Order By: Relevance
“…For example, in a study with 326 British youth sport participants, results indicated that coach behaviours satisfying the need for autonomy were related to all eight life skills in the LSSS. 63 In the current study, all life skills factors of the LSSS-C were positively correlated with competence supportive coaching behaviours. In addition, autonomy supportive coaching behaviours were positively related to social skills, emotional skills, leadership, and time management, and relatedness supportive coaching behaviours were positively correlated with social skills, emotional skills, and problem solving.…”
Section: Discussionsupporting
confidence: 48%
“…For example, in a study with 326 British youth sport participants, results indicated that coach behaviours satisfying the need for autonomy were related to all eight life skills in the LSSS. 63 In the current study, all life skills factors of the LSSS-C were positively correlated with competence supportive coaching behaviours. In addition, autonomy supportive coaching behaviours were positively related to social skills, emotional skills, leadership, and time management, and relatedness supportive coaching behaviours were positively correlated with social skills, emotional skills, and problem solving.…”
Section: Discussionsupporting
confidence: 48%
“…Achados semelhantes são observados em praticantes de esportes coletivos (Mossman & Cronin, 2019;Cronin & Allen, 2017) e praticantes de educação física escolar (Cronin et al, 2019). Nesse cenário, os achados do presente estudo corroboram os encontrados na literatura, demonstrando que a prática de esportes individuais tem papel fundamental para o desenvolvimento das habilidades para vida Cronin et al, 2019;Cronin et al, 2018).…”
Section: Discussionunclassified
“…In recent years, positive interventions in favor of the development of young people have sought to address the determinants of health risk behaviors of adolescents, with sports being one of the areas that contribute to the positive young development (PYD) (Johnston et al, 2013;Pierce, Gould, & Camiré. 2017;Cronin et al, 2018;Camiré et al, 2019;Cronin et al, 2019). PYD's approach postulates that all young people have the potential for positive, successful and healthy development throughout adolescence (Lerner et al, 2005;Lerner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%